Chemical and Physical Characterization of Swift Guano in Quartzitic Karst Landscape in Brazil - Reis, André Luiz Miranda; Clemente, Nicolo; Faria, André Luiz Lopes de; Bernardes, Rodrigo Cupertino; Costa, Liovando Marciano da (Sociedade & Natureza, 2023)
The Private Reserve of Natural Patrimony (RPPN) of the Santuário of Caraça is found in a mountain region within the Quadrilátero Ferrífero geological province in the State of Minas Gerais. In this region, intense metamorphic processes shaped their siliciclastic rocks, enabling the formation of fractures and diaclasis, the favourite routes of weathering during the development of karst landscapes. The natural cavities thus formed, mainly in the RPPN sector called “Pico do Inficionado”, provide shelter for countless swifts of the species Streptoprocne zonaris and S. biscutata, responsible for the accumulation of guano on the floor. However, guano is a substance rich in nutrients, mainly phosphates and nitrates, and this is the main nutrient supply in permanently dry caves. This work studied the physical (density) and chemical (organic carbon, nitrogen, potassium, phosphorus, sodium, calcium, magnesium, aluminium and pH) characteristics of 21 guanos layers, correlating their contents with the depth of seven deposits and separating the results into factors. Considering that, knowing that the guano deposits contain crucial elements such as Ca, Mg, and especially P and N, which act as an energy source for many chemotrophic organisms, the subdivision of the studied elements allowed us to defer three factors: the first one features the concentrations of Al, P, K, Na and CO, the second one was determined for N, pH and density. Finally, the third factor was based on Ca and Mg. The quartzitic material influences the chemical and physical composition of the deepest guano. As the rock changes, elements like Al and K are released and enrich the deeper layers, as well as increasing density due to the presence of sand in the material.